Detrminan Kualitasl Laporanl Keuangan Pemerintah Daerah (Studi KasuslPada BPPKAD Kabupaten Situbondo) - findy Indahmanisya Pujiharjo findy; Arik Susbiyani; Retno Murwanti (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
The problem studied by the author is regarding the influence of human resource competence related to the preparation of financial reports, and the application of the internal control system at BPPKAD Situbondo Regency. The purpose of this study was to determine the effect of human resource competence related to the preparation of financial reports, and the application of an internal control system to the quality of financial reports at BPKAD Situbondo Regency. The data analysis technique used was a quantitative approach. Data was collected by distributing questionnaires to 50 respondents and 44 respondents from the questionnaire results were received back to be processed by selecting samples using purposive sampling. Tests carried out using validity and reliability tests. Data processing was analyzed using descriptive statistics with multiple linear regression analysis techniques using SPSS. Based on the results of the study concluded that Human Resource Competence (HR) has a significant influence on the Quality of Local Government Financial Reports (LKPD) and the Implementation of Internal Control Systems (SPI) has a significant influence on the Quality of Local Government Financial Reports (LKPD).